2019
DOI: 10.1063/1.5083138
|View full text |Cite
|
Sign up to set email alerts
|

A human proximal tubule-on-a-chip to study renal disease and toxicity

Abstract: Renal disease is a global problem with unsustainable health-care costs. There currently exists a lack of accurate human renal disease models that take into account the complex microenvironment of these tissues. Here, we present a reusable microfluidic model of the human proximal tubule and glomerulus, which allows for the growth of renal epithelial cells in a variety of conditions that are representative of renal disease states including altered glomerular filtration rate, hyperglycemia, nephrolithiasis, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 51 publications
0
53
0
Order By: Relevance
“…The chip was applicable for nephrotoxicity assessments, therapeutic development, regenerative medicine, and kidney development and disease. Sakolish et al [77] produced a reusable microfluidic chip in human proximal tubules and glomeruli that permitted renal epithelial cells to grow under various conditions. Shear stress causes nephrotoxicity.…”
Section: Kidney Ooacmentioning
confidence: 99%
“…The chip was applicable for nephrotoxicity assessments, therapeutic development, regenerative medicine, and kidney development and disease. Sakolish et al [77] produced a reusable microfluidic chip in human proximal tubules and glomeruli that permitted renal epithelial cells to grow under various conditions. Shear stress causes nephrotoxicity.…”
Section: Kidney Ooacmentioning
confidence: 99%
“…In addition to providing a shear-stressed culture environment for HK-2 cells, the platform contained a glomerular filter containing HUVECs to provide a more realistic "primary urine" inside the device. Later, the group used such a platform to evaluate the DIN by cisplatin and cyclosporine [82]. The results show that HK-2 cells cultured in this microfluidic device are more sensitive.…”
Section: Kidney-on-a-chip For Drug Nephrotoxicity Testingmentioning
confidence: 99%
“…The results show that HK-2 cells cultured in this microfluidic device are more sensitive. Musah et al demonstrated that fluid shear stress could promote the proximal tubular epithelial cells (PTECs) to retain more mature phenotypes and develop a glomerulus-on-a-chip model [82]. Weber and his team [83] combined the single-channel Norvatis microphysiology system (MPS) and the PTECs to reconstruct the physiological function of human proximal tubules in vitro and used this platform to evaluate the nephrotoxicity of polymyxin antibiotics.…”
Section: Kidney-on-a-chip For Drug Nephrotoxicity Testingmentioning
confidence: 99%
“…This technology was helpful to reproduce the in vivo cisplatin and gentamicin toxicity, demonstrating that the once-a-day bolus dosing method was less nephrotoxic than the continuous infusion method [137]. Moreover, the combination of tubule-on -a-chip systems with innovative detection methods to analyze novel biomarkers specific for nephrotoxicity identifies this technology as a fully compatible platform with automation and high content screening equipment [134][135][136][137][138][139][140][141]. However, the goal standard in understanding nephrotoxicity is the integration of multiple cell types from different organs.…”
Section: Tubule-on-a-chipmentioning
confidence: 99%